2020
DOI: 10.1007/s11142-020-09545-w
|View full text |Cite
|
Sign up to set email alerts
|

The effects of MiFID II on sell-side analysts, buy-side analysts, and firms

Abstract: Nimé for excellent research assistance. We are grateful to Drago Sab u, Java software developer, for the application that extracts the conference call participants, and to FactSet for providing the conference call transcripts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 75 publications
3
28
0
Order By: Relevance
“…There is empirical evidence that shows a decrease in the European stock market liquidity following MiFID II. This decrease is justified in the previous studies with a decrease in the analyst coverage due to the unbundling research provision in MiFID (Utkilen and Wakeford-Wesmann 2019;Fang et al 2020;Anselmi and Petrella 2021;Guo and Mota 2021). To our knowledge, there are no similar studies up to this date that have investigated the effects of MiFID II on liquidity in the Romanian stock market, while the impact of MiFID II on other European stock markets is scarcely addressed, partly due to the complex measures of MiFID II and the early point of analysis.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…There is empirical evidence that shows a decrease in the European stock market liquidity following MiFID II. This decrease is justified in the previous studies with a decrease in the analyst coverage due to the unbundling research provision in MiFID (Utkilen and Wakeford-Wesmann 2019;Fang et al 2020;Anselmi and Petrella 2021;Guo and Mota 2021). To our knowledge, there are no similar studies up to this date that have investigated the effects of MiFID II on liquidity in the Romanian stock market, while the impact of MiFID II on other European stock markets is scarcely addressed, partly due to the complex measures of MiFID II and the early point of analysis.…”
Section: Introductionmentioning
confidence: 77%
“…Recent studies have shown that both quantity and quality of analyst research have been affected by the MiFID II provisions regarding research unbundling. Although the quality of the research seems to have improved, the quantity of the research and the firm's analyst coverage seems to have dropped, according to the documented connection between analyst coverage and liquidity of the stock market (Roulston 2003), and a reduction of the latter (Utkilen and Wakeford-Wesmann 2019;Fang et al 2020;Anselmi and Petrella 2021;Lee 2018).…”
mentioning
confidence: 99%
“…While there is little empirical evidence that shows a decrease in the European stock market liquidity following MiFID II (Fang et al 2020;Utkilen and Wakeford-Wesmann 2019;Anselmi and Petrella 2020), there are only a handful of studies that have approached the impact of the implementation of MiFID II on the volatility of European Union stock markets. Meijers (2018) investigated whether the pre-and post-trade transparency requirements imposed through MiFID I and MiFID II/MiFIR led to reduced volatility in European equity markets, considering three stock market indexes.…”
Section: Dalymentioning
confidence: 99%
“…On the other hand, one of the most important goals of MiFID II was to secure a high level Laws 2021, 10, 55 2 of 11 of market transparency and fairness. This is meant to address the potential conflicts of interest in the financial services industry, which is in the best interest of the investors (Fang et al 2020). The pre-trade and post-trade increased transparency demanded in the MiFID II should have also impacted the volatility of the stock markets, given the existing association between volatility and accuracy of stock prices.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, our analysis and market transparency. There is also recent research examining the preliminary impacts of MiFID II on the supply of sell-side research (Fang, Hope, Huang, and Moldovan (2019); Guo and Mota (2019); Lang, Pinto, and Sul (2019)). Evidence from Guo and Mota (2019) suggests that the implementation of MiFID II led to a 7.45% decline in research coverage in Europe.…”
Section: Ia Related Literaturementioning
confidence: 99%